A Reliable Quantification Method for Trimethoprim in Pharmaceutical Samples by HILIC-HPLC (Indian Journal of Forensic Medicine & Toxicology, 2020)
Trimethoprim is sometimes used in conjunction with sulfonamides for drug therapies Herein. A practicablemethod has been developed to determine trimethoprim in pharmaceutical formulations by hydrophilicinteraction liquid chromatography coupled with an ultraviolet detector. The development and investigationof a new HLIC assay of trimethoprim. The separation was made in the HALO-HILIC column using aNaOAc/HAc buffer (40 mM-pH 4.75) with acetonitrile (10:90) (v/v) as mobile phase and was quantifiedby UV detection at 280 nm. The limit of quantification was about 0.0242 ppm and the limit of detection0.008 ppm. The calibration curves were linear in the investigated range (0.01-3 ppm). The recovery oftrimethoprim was 99-102.5%. The method was applied in pharmaceutical formulations.